Futures-Trading Activity and Stock Price Volatility. - Bessembinder, Hendrik; Seguin, Paul J (Journal of Finance, 1992)
The authors examine whether greater futures-trading activity (volume and open interest) is associated with greater equity volatility. They partition each trading activity series into expected and unexpected components, and document that while equity volatility covaries positively with unexpected futures-trading volume, it is negatively related to forecastable futures-trading activity. Further, though futures-trading activity is systematically related to the futures contract life cycle, the authors find no evidence of a relation between the futures life cycle and spot equity volatility. These findings are consistent with theories predicting that active futures markets enhance the liquidity and depth of the equity markets.